PENERAPAN RUANG HENTI KHUSUS SEPEDA MOTOR PADA PERSIMPANGAN BERSINYAL - Muhammad Idris (Jurnal Jalan-Jembatan, 2009)
The Exclusive Stopping Space for Motorcycles is defined as facilities for motorcycle to stop for waiting at signalized intersection as long as red traffic light period. The RHK's has been tested in an arterial road to support the movement of the motorcycle at the signalized intersection. This paper aims to study the influence of the RHKs to reduce traffic conflict, particularly the type and intensity of conflict and also the severity of conflict between motorcycles with another motor vehicle. To test the affectivity of RHKs to reduce conflict, the traffic conflict observations were made with video cameras during the morning and afternoon peak hours, before and after installing the RHKs, and the analyses were carried out in the laboratory. A total of 62 cycles and 41 cycles in the morning and afternoon peak hour with total of 12214 motorcycles and 8873 motorcycles (before and after RHKs installed) were analyzed. The throughput of the intersection increased both in the morning and afternoon peak hours by respectively 11.92% and 12.31%. The conflict patterns changed significantly, but the conflict rate decreased from 133,39 conflict/1000 pcu's to 24,68 conflict/1000 pcu's on the morning peak hour and from 111,10 conflict/1000 pcu's to 24,10 conflict/1000 pcu's on the afternoon peak hour. The conflict severity also decreased from 1.83 tp 1.43 on the morning peak hour and 1.86 to 1.38 on the afternoon peak hour. Keyword : RHK's (ESSM : Exclusive Stopping Space for Motorcycle), motorcycle, traffic, conflict, conflict rate, conflict severity